Save Energy by Refurbishing and Coating Pumps. Issue 10 (1st October 2015) - Maier, Paul; King, Chris; Metzger, Richard
Abstract : Monroe County Water Authority (N.Y.) discovered that coating pumps prevents or at least impedes a decline in pump performance and corresponding increase in energy consumption from internal corrosion and tuberculation buildup.